2015
DOI: 10.1074/mcp.m114.042242
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics of Skin Proteins in Psoriasis: From Discovery and Verification in a Mouse Model to Confirmation in Humans

Abstract: Herein, we demonstrate the efficacy of an unbiased proteomics screening approach for studying protein expression changes in the KC-Tie2 psoriasis mouse model, identifying multiple protein expression changes in the mouse and validating these changes in human psoriasis. KC-Tie2 mouse skin samples (n ‫؍‬ 3) were compared with littermate controls (n ‫؍‬ 3) using gel-based fractionation followed by label-free protein expression analysis. 5482 peptides mapping to 1281 proteins were identified and quantitated: 105 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 38 publications
2
31
0
1
Order By: Relevance
“…Psoriasis is marked by gross histologic alterations (Lowes et al , 2014) that are accompanied by pervasive transcriptomic (Jabbari et al , 2012; Li et al , 2014; Swindell et al , 2013) and proteomic (Lundberg et al , 2015; Swindell et al , 2015) changes in inflamed skin. However, global metabolic changes have not previously been addressed in psoriatic skin.…”
Section: Discussionmentioning
confidence: 99%
“…Psoriasis is marked by gross histologic alterations (Lowes et al , 2014) that are accompanied by pervasive transcriptomic (Jabbari et al , 2012; Li et al , 2014; Swindell et al , 2013) and proteomic (Lundberg et al , 2015; Swindell et al , 2015) changes in inflamed skin. However, global metabolic changes have not previously been addressed in psoriatic skin.…”
Section: Discussionmentioning
confidence: 99%
“…Using qPCR, we confirmed that six of these 10 genes were indeed significantly differentially expressed. Otx1 and Tekt2 play a role in inner ear development; Scg2 (also known as secretoneurin) interacts with STAT3, a known ISL1‐interaction partner; Ptprv is associated with bone and energy metabolism, as well as P53‐induced cell cycle exit; Pdzk1ip1 (or Pdzk1 ‐interacting protein 1) also interacts with Twist1, an important regulator of the Bmp signaling pathways; and Stfa1 was observed to be overexpressed in a mouse psoriasis model . Moreover, Otx1 , Ptprv , and Scg2 are all expressed in E14.5 incisor tooth germs (http://genepaint.org/Frameset.html).…”
Section: Resultsmentioning
confidence: 99%
“…Pdzk1ip1 (or Pdzk1-interacting protein 1) also interacts with Twist1, an important regulator of the Bmp signaling pathways (57) ; and Stfa1 was observed to be overexpressed in a mouse psoriasis model. (58) Moreover, Otx1, Ptprv, and Scg2 are all expressed in E14.5 incisor tooth germs (http://genepaint.org/ Frameset.html). The remaining four genes, Kif27a, Frem3, Shisa7, and Hmgn2, showed similar trends to the RNA-Seq results but did not reach statistical significance (Fig.…”
Section: Rna-seq Analysis Points To Numerous Differentially Expressedmentioning
confidence: 99%
“…These approaches have been highly successful in helping us to determine the general composition of the SC but each has their limitations. The use of mass spectrometry-based 'omic' approaches is on the increase for investigating skin biochemistry especially proteomics [13][14][15][16][17][18][19]. Recently, these methods have been used to determine differences in the corneome of dry skin on the leg of post-menopausal women and dandruff on the scalp [20][21][22].…”
Section: Introductionmentioning
confidence: 99%